Regulating artificial intelligence in Malaysia: the two-tier approach - Abdul Manap, Nazura; Abdullah, Azrol (UUM Press, 2020)
Artificial Intelligence (AI) has been developed under the field of computer science for more than 50 years. AI somehow only gains its prominence in the recent millennia when the necessary tools to test the hypothesis on nature of thought became available. Unfortunately, the absence of legal regulation on AI has caused AI to exist in a regulatory vacuum and nature abhors vacuum. The law is at the state of confusion about who shall be blameworthy for the damage caused by AI. The prevalence of this problem triggers for the expatiation of this review article in defining the scope of AI that must be regulated. The objective of this article is to suggest that AI with certain capabilities must be placed in the legal realm. This article will first begin by highlighting the problems associated with AI before directing the focus of the discussion to the various reasons that justify for AI to be regulated. This article will then explore the various approaches which can be adopted by government in regulating AI. These approaches can be a workable formula to procure the two-tier methods in regulating AI in Malaysia. The methodology devised for this article is based on doctrinal research where most of the materials are derived from text books, online resources and established academic databases. The findings made in this article suggest that AI must be regulated independently from the existing legal framework. Reason being, AI capabilities are unique in its own sense and therefore cannot be treated like other previous technologies. The outcome of this article will also able to contribute on issues relating to the legal liability of AI in Malaysia.